PENGEMBANGAN BAHAN AJAR BERBASIS KOMIK EDUKASI PADA MATA PELAJARAN IPS UNTUK KELAS V SDN 1 KURIPAN UTARA - Aprianti, Lisa; Nurhasanah; Hasnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The use of creative and innovative teaching materials in learning has a very important role so that it can increase students' interest in learning and be able to make it easier to understand learning materials, especially in social studies learning. This study aims to produce a product in the form of comic-based educational materials for IPS lessons that cover various types of community economic activities for Class V of SDN 1 Kuripan Utara, which are valid and practical. The type of research used is Research and Development (R&D) with a research model used being the 4D model, which consists of four stages: Define (definition), Design (design), Development (development), and Disseminate (dissemination). This study was conducted at SDN 1 Kuripan Utara. The subjects of the study were 8 fifth-grade students at SDN 1 Kuripan Utara. The object of the study was comic-based educational materials for IPS lessons on the topic of types of community economic activities. The research methods used in this study are questionnaires, in the form of expert media and material validation questionnaire and teacher and student response questionnaire. The results of this study are based on expert media validation tests, which yielded a score of 83.63% with a very valid criterion. The results of the expert material validation test yielded a score of 81.25% with a very valid criterion. Then, based on the practicality test according to the teacher's response, the result was 89% with a very practical criterion. Similarly, the result of the student's response was 81% with a very practical criterion. Therefore, it can be concluded based on the research results that the comic-based educational materials developed are feasible to used for teaching IPS lessons on the topic of types of community economic activities for Class V of SDN 1 Kuripan Utara.